2020
DOI: 10.1101/2020.07.17.208603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutrient signaling, stress response, and interorganelle communication are non-canonical determinants of cell fate

Abstract: Isogenic cells can manifest distinct cellular fates for a single stress, however the nongenetic mechanisms driving such fates remain poorly understood. Here, we implement a robust multi-channel live-cell imaging approach to uncover noncanonical factors governing cell fate. We show that in response to acute glucose removal (AGR), budding yeast undergo distinct fates becoming either quiescent or senescent. Senescent cells fail to resume mitotic cycles following glucose replenishment but remain responsive to nutr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This might be the case for other scenarios of cumulative cellular damage, for instance during cellular ageing (Chen et al, 2020(Chen et al, , 2021Li et al, 2020;Moreno and Aldea, 2020;Mouton et al, 2020). Though NVJs are not essential to drive entry into quiescence upon glucose starvation, prominent NVJ expansion seems to accompany this transition (Wood et al, 2020). Cells can persist in a quiescent state for a long time, awaiting re-entry into cell cycle upon more favourable conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This might be the case for other scenarios of cumulative cellular damage, for instance during cellular ageing (Chen et al, 2020(Chen et al, , 2021Li et al, 2020;Moreno and Aldea, 2020;Mouton et al, 2020). Though NVJs are not essential to drive entry into quiescence upon glucose starvation, prominent NVJ expansion seems to accompany this transition (Wood et al, 2020). Cells can persist in a quiescent state for a long time, awaiting re-entry into cell cycle upon more favourable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies on the dynamic remodelling and physiological relevance of NVJs highlight these contact sites as hubs to integrate metabolic cues and stress responses to determine cellular fate (Hariri et al, 2018;Lord and Wente, 2020;Wood et al, 2020;Tosal-Castano et al, 2021). While compromised NVJ formation remains without major effect on cellular viability in unperturbed cells (Wood et al, 2020), disruption of specific aspects of proteostasis, as shown for deficiencies in NPC assembly (Lord and Wente, 2020), necessitate efficient NVJ formation for survival. This might be the case for other scenarios of cumulative cellular damage, for instance during cellular ageing (Chen et al, 2020(Chen et al, , 2021Li et al, 2020;Moreno and Aldea, 2020;Mouton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations